Pemanfaatan City Tour sebagai Sumber Belajar dalam Mata Pelajaran Tour Guiding di Kelas XI Jurusan Usaha Perjalanan Wisata di SMK Negeri 57 Jakarta - RA Murti Kusuma Wirasti; Santi Maudiarti; Nadia Qurotha (Jurnal Pembelajaran Inovatif, 2019)
This study aims to describe the utilization of city tour on tour guiding subject in grade XI tourism program at SMK Negeri 57 Jakarta. The method used in this study is descriptive qualitative with case study approach and data collection techniques through questionnaire, interview, observation and documentation. The result of this study indicates that the teacher has taken advantage of city tour as a source of learning on tour guiding subject grade XI. Data obtained are described in percentage and narrative analysis. The utilization of city tour is described through the six steps of utilization model ASSURE which includes 1) Analyze learners, 2) Select objective, 3) Select method, media and materials, 4) Utilize media and materials, 5) Require learners’ participation, 6) Evaluate and revise.